1987
DOI: 10.1002/1098-108x(198711)6:6<741::aid-eat2260060607>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Social impairment in bulimia

Abstract: The Social Adjustment Scale‐Self‐Report (SAS‐SR) was used to compare the social adjustment of 30 bulimic women with 30 female controls of similar age, level of education, economic class, and marital status. The bulimic population was significantly more impaired than the control group on the work, social/leisure, extended family, and overall subscales of the SAS‐SR. There were 68% of the bulimics who scored within the clinically impaired range on at least one of the subscales compared with 13% of the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Studies looking at women with an eating disorder show largely similar results (Katzman, 1985;Soukup et al, 1990;Yager, Rorty, & Rossotto, 1995). A number of other studies have also suggested that bulimic subjects have poor levels of social adjustment, difficulty with interpersonal relationships, and lack social support (Striegel-Moore, Silberstein, & Rodin, 1993;Herzog, Keller, Lavori, & Ott, 1987;Van den Broucke, Vandereycken, & Vertommen, 1995;Tiller et al, 1997). However, these studies have all used trait measures of coping and it is uncertain how far these predict coping in response to specific problems (Lazarus & Folkman, 1984).…”
Section: Introductionmentioning
confidence: 83%
“…Studies looking at women with an eating disorder show largely similar results (Katzman, 1985;Soukup et al, 1990;Yager, Rorty, & Rossotto, 1995). A number of other studies have also suggested that bulimic subjects have poor levels of social adjustment, difficulty with interpersonal relationships, and lack social support (Striegel-Moore, Silberstein, & Rodin, 1993;Herzog, Keller, Lavori, & Ott, 1987;Van den Broucke, Vandereycken, & Vertommen, 1995;Tiller et al, 1997). However, these studies have all used trait measures of coping and it is uncertain how far these predict coping in response to specific problems (Lazarus & Folkman, 1984).…”
Section: Introductionmentioning
confidence: 83%
“…In terms of the friendship network, it is fairly well documented that bulimic women report impaired functioning in the area of social and leisure activities (Derogatis, Lipman, Rickels, Uhlenhuth, & Covi, 1974;Herzog, Keller, Lavori, & Ott, 1987;Herzog, Pepose, Norman, & Rigotti, 1985;Johnson & Berndt, 1983). Furthermore, Mintz ( 1982) has reported several clinical cases of individuals whose friendship networks were very limited because of difficulties with peer relationships.…”
Section: Pikementioning
confidence: 99%
“…The emerging consensus among investigators is that bulimia is a multidetermined disorder with a number of contributing factors, including biological components, sociocultural factors, and personality and family characteristics. One area of research has indicated that the relationship between bulimics and their environment is disturbed, in that bulimics demonstrate social impairment and dissatisfaction with their social support and relationships (Garner & Olmsted, 1984;Herzog, Keller, Lavori, & Ott, 1987;Herzog, Norman, Rigotti, & Pepose, 1986;Johnson & Berndt, 1983;Johnson & Maddi, 1986). Other researchers have documented the conflicted, hostile, and chaotic relationships in bulimic families (Garner, Garfinkel, & Olmsted, 1983;Humphrey, 1986;Humphrey, Apple, & Kirschenbaum, 1985), and social support research has highlighted the importance of considering such negative interactions when assessing social support (Abbey, Abramis, & Caplan, 1985;Rook, 1984).…”
mentioning
confidence: 99%